ANALYSIS OF MATHEMATICS ANXIETY: A CASE STUDY ON STATISTICS COURSES ACROSS DISCIPLINES - Nathasa Pramudita Irianti; Kardiana Metha Rozhana; Nila Kartika Sari (Inteligensi : Jurnal Ilmu Pendidikan, 2026)
This study examines mathematics anxiety among students in the Land Study Program at Politeknik Agraria STPN when taking the Statistics course. Using a qualitative descriptive case study design, data were collected from 40 second-semester students through a questionnaire adapted from the Mathematics Anxiety Rating Scale (MARS) and in-depth interviews with 12 students identified as having high anxiety levels. Results show that 87,5% of students experienced moderate to high mathematics anxiety, driven mainly by a weak mathematical background, limited independent study time, and the added complexity of connecting statistical concepts to land measurement data such as coordinates and spatial interpolation. Anxiety was most frequently triggered by oral questioning from lecturers and evaluative situations such as exams. Students proposed strengthening self-efficacy and adopting contextual, field-based learning as the most promising solutions. These findings confirm that mathematics anxiety among non-mathematics students is shaped not only by general affective and cognitive factors but also by discipline-specific demands. The study recommends that statistics instruction in the Land Study Program be designed around authentic land administration cases to build both competence and confidence, while lecturers adopt evaluation methods that reduce anxiety-provoking pressure during class interactions.